Closing & Keynote sessions: Agriculture, Landscapes and Livelihoods Day - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Filmed Live at Agriculture, Landscapes and Livelihoods Day 5, 3 December 2012 in Doha, Qatar. http://www.agricultureday.org Perspectives from the Committee on World Food Security - Tewolde Gebre Egziabher, High Level Panel of Expert Steering Committee member, Head of the Environment Protection Agency of Ethiopia - Franklin Moore, Vice Chair of the Committee on Food Security, USAID Deputy Assistant Administrator for Africa Wrap up of the day: Robynne Anderson Closing High Level Keynote: Outlook on 2013 - Honourable Mduduzi Duncan Dlamini, Minister of Tourism and Environmental Affairs, Kingdom of Swaziland